Species Diversity and Dominance of the Aranaemorphae Sub-Order in the 90-Day-Old Rice Generative Phase - Putra, Ichsan Luqmana Indra; Pertiwi, Pelangi Mayang Sukma (Journal of Biotechnology and Natural Science, 2022)
Spiders have an important role in ecosystems, in particular agricultural ecosystems. Spiders play the role of natural enemies capable of helping farmers by eating insect pests. The purpose of this study was to identify the type of Sub-Order Aranaemorphae and calculate the level of diversity and dominance of the type of Sub-Order Aranaemorphae in the generative phase of rice aged 90 days. The study was conducted in April-September 2022 in the rice field area of Tamanan Village. The determination of the research location was carried out using the purposive sampling method with the criteria of a rice field area of 2500 m2 and the age of rice plants ranging from 90 days. Sampling was carried out on 9 plots with a plot size of 21 x 4 m2 each. Sampling was carried out by hand picking and indirect methods with sweep nets, pitfall traps, and yellow pan traps. The species of Sub-Order Aranaemorphae found in this study were 12 species, namely Oxyopes sp., O. lineatipes, O. javanus, Atypena formosana, Tetragnatha vermiformis, Pardosa pseudoannulata, Lycosa sp., L. pseudoannulata, Lycosa sp. 1, Araneus inustus, Clubiona  sp.  and Thomisus  Sp. The conclusion of this study were the diversity index value (H') of the Aranaemorphae Sub-Order obtained in this study was 2.133 with a moderate category, and the dominance index value (D) of the Aranaemorphae Sub-Order obtained was 0.1785 with a low category. The total number of spider individuals obtained was 173 individuals.